Source waste separation behavior among Shah Alam households / Carol Boon Chui Teo ... [et al.] - Boon, Carol Chui Teo; Abdul Karim, Azra Syakira; Mamud, Nur Afieqah; Wan Abdul Hamid, Wan Norhanis Hanini (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2018)
One of the main contentious recycling issues in Malaysia is household solid waste management. With solid waste buildup and bottlenecks reaching its limit at landfills, local councils face uphill tasks to manage it. Solid source waste separation (SWS) for households was first officially enforced across eight states in Malaysia on 1 June 2016. However, Selangor has yet to enforce this system and is left to selected local councils to embark on pilot projects. It has been iterated that Selangor which has the largest population in Malaysia should adopt the law on mandatory SWS for households as it is already facing a garbage disposal crisis. Previous studies have been documented on recycling behavior but few delve into SWS. This paper examines household behavior towards SWS intention at Shah Alam. Based on the Theory of Planned Behavior, influences of attitude (ATT), subjective norms (SN) and perceived behavior control (PBC) towards SWS were determined. Methodology utilized interviews with two local councils and observations on household recycling behavior. Survey was administered on 150 households. Using PLS analysis, results indicate ATT and PBC have positive and significant influences on SWS intention while subjective norm was not significant. Findings had some implications on strategies for local councils in managing SWS system.